THE ROLE OF FORMING PERSONAL CONSCIOUSNESS IN ENSURING SUSTAINABLE DEVELOPMENT OF SOCIETY (World Bulletin of Social Sciences, 2024)
This article analyzes the concepts of “consciousness” and “thinking” from the point of view of psychology and neurophysiology, emphasizing the special role of the socio-psychological climate and other social factors in the formation of information and psychological security of society.